Increased pregnancy rate using standardized coculture on autologous endometrial cells and single blastocyst transfer : a multicentre randomized controlled trial - Ohl, J; de Mouzon, J; Nicollet, B; Benoussaí¯dh, A; Gouze, J N; Viville, S; Menezo, Y (Cellular and Molecular Biology, 2015)
Despite excellent published results, the lack of well-designed, multicentre, randomized clinical trials results in an absence of general consensus on the efficacy of autologous endometrial cells coculture (AECC) in Assisted Reproductive Technology (ART). An open, multicentre, prospective, randomized controlled trial was designed to compare the pregnancy rate (PR) after the transfer of one blastocyst on day 5 after AECC to the transfer of one embryo on day 3 (control group). Patients were women aged 18 to 36, undergoing an ART cycle with no more than 1 embryo transfer failure. Sample size was calculated at 720 for a superiority trial involving an intermediate analysis at 300 patients. We present the results of the intermediate analysis that resulted in the study ending considering the observed difference. Three hundred thirty nine patients were randomized: 170 in the AECC group and 169 in the control group. The clinical PR per transfer was 53.4% with AECC and 37.3% in the control group (p=0.025). The quality of embryos was improved with AECC. These results suggest that implementation of the AECC technique to a large number of In-Vitro Fertilization (IVF) centres could lead to a substantial improvement in the proportion of successful assisted reproduction. The study was supported by the Laboratoires Genévrier, France.